True Story Project: I Am Heard: Empowering Female Adolescents with Physical Disabilities through Creative Expression - Xenakis, Nancy; Goldberg, Judith; Treston, Elizabeth (Disability Studies Quarterly, 2012)
This article introduces the creative writing component of the Young Women's Program (YWP), a comprehensive health and wellness program that serves young women, ages 14-21, with physical disabilities. The YWP is a part of the Initiative for Women with Disabilities (IWD), a hospital-based center in New York City serving women across the life span with physical disabilities/conditions. The goal of the YWP, established in 2006, is to help young women develop a better sense of self and respect and honor their bodies by adopting healthy lifestyles. The creative writing workshop of the YWP, True Story Project: I Am Heard (TSP) focuses on helping select program participants find their voices and share their stories through writing. This article describes the design, content and purpose of TSP, shares several of the young women's narratives, and includes a reflective analysis by the young women and facilitators of their experiences in the program and its impact on their lives. Keywords: physical disabilities; young women; creative writing; self-expression; empowerment; self-esteem